2014
DOI: 10.4034/pboci.2014.142.06
|View full text |Cite
|
Sign up to set email alerts
|

Dental Health Knowledge and Attitudes of Primary School Teachers Toward Dental Health Education in Maceió, Brazil

Abstract: Objective: To evaluate the levels of knowledge and attitudes toward oral health of preschool teachers of Maceió, Alagoas. Material and Methods: Cross-sectional study using a pretested structured questionnaire (32 teachers equivalent to 20% of the sample) applied to 140 teachers of Child Day Care Centers of Maceió. To assess the level of information of survey participants (dependent variable), frequency from 0 to 49.99% of correct answers of questions proposed was considered unsatisfactory knowledge; 50 to 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“… 23 A reliable oral health instruction program must encourage the addition of subjects, knowledge, and practices. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 23 A reliable oral health instruction program must encourage the addition of subjects, knowledge, and practices. 24 …”
Section: Discussionmentioning
confidence: 99%
“…O conhecimento dos profissionais de educação que t raba lha m com esse público ta mbém é limitado no que diz respeito à saúde bucal [26]. No entanto o trabalho dos centros educacionais não se limita apenas a educar, mas também permite o desenvolvimento e percepção de atitudes conscientes em relação ao próprio cuidado [15,24].…”
Section: Inter-relação Educação E Saúde Bucalunclassified
“…They concluded that teachers showed poor knowledge of the etiology of periodontal diseases. [ 13 ] In Northern Israel, a study was conducted among Arab school teachers. The study revealed that the teachers had positive attitudes toward enlightening the parents about the importance of oral hygiene and tutoring the children about preventive dentistry while that they were less motivated about being involved in dental health school programs.…”
Section: Introductionmentioning
confidence: 99%